2015 38th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) 2015
DOI: 10.1109/mipro.2015.7160456
|View full text |Cite
|
Sign up to set email alerts
|

Predicting stock market trends using random forests: A sample of the Zagreb stock exchange

Abstract: Stock market prediction is considered to be a challenging task for both investors and researchers, due to its profitability and intricate complexity. Highly accurate stock market predictive models are very often the basis for the construction of algorithms used in automated trading. In this paper, 5-days-ahead and 10-days-ahead predictive models are built using the random forests algorithm. The models are built on the historical data of the CROBEX index and on a few companies listed at the Zagreb Stock Exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…(2.1). Another commonly used measure for prediction performance is the percent correctly classi¯ed (PCC) as in studies by Kumar et al (2006), Kim (2003) and Manojlovic et al (2015). The PCC is computed using equation as depicted in Eq.…”
Section: Prediction Model Evaluationmentioning
confidence: 99%
“…(2.1). Another commonly used measure for prediction performance is the percent correctly classi¯ed (PCC) as in studies by Kumar et al (2006), Kim (2003) and Manojlovic et al (2015). The PCC is computed using equation as depicted in Eq.…”
Section: Prediction Model Evaluationmentioning
confidence: 99%
“…They suggested that using Lexicon based approach can increase the accuracy of the algorithm. In the research paper named Predicting stock market trends using random forests [3]T.Manojlovic and I. Stajduhar used the Random forest algorithm for the Stock Price prediction ,in results it is concluded that the prediction efficiency of algorithm is 60%.They suggested that for future research using Hybrid Model can increase the accuracy of the algorithm. In the research paper named Stock price prediction using regression based sentiment analysis [4]Yahya Eru Cakra and Bayu Distiawan Trisedya used the Linear Regression for the Stock Price prediction ,in results it is shown that the prediction efficiency of algorithm is 86.12.They suggested that Can improve accuracy using POS tagging and word weighting can increase the accuracy of the algorithm.…”
Section: Literature Surveymentioning
confidence: 99%
“…[23] have showcased that a simple artificial neural network (76%) had a better accuracy over an SVM kernel (72%). Logistic regression, K-nearest neighbors [37], random forests [28] have also been some of the traditional machine learning algorithms investigated by the researchers but the results have not been promising.…”
Section: Introductionmentioning
confidence: 99%